Chronic Hypotension in Dialysis is a Prognostic Factor in the Evolution of Kidney Transplantation. (July 2018) - Auñón, Pilar; García, Ana; Gutiérrez, Eduardo; Morales, Enrique; Praga, Manuel; Andrés, Amado
Abstract : Introduction: 5-10% of hemodialysis patients have chronic hypotension (interdialysis). The pathophysiological mechanisms are unclear. Chronic hypotension represents great comorbidity for these patients. Some authors have suggested that the hemodynamic condition is also a decisive factor for the results of renal transplantation, relating chronic hypotension to primary non-graft function due to venous thrombosis. Different interventions aimed at improving this hemodynamic situation could improve renal prognosis in this group of patients. We analyze the evolution of hypotensive patients transplanted in our center. Material and Methods: It is a retrospective cohort study. Renal transplants performed at Hospital Doce de Octubre between 2004 and 2013 were analyzed. Fifty-two patients with chronic hypotension (defined as Systolic Blood Pressure ⩽ 100 mmHg at the time of transplantation) were identified from the total of 1503 kidney transplants performed during this period. A control group of 52 non-hypotensive transplants was assigned. The evolution of both groups was compared in terms of primary graft function, graft thrombosis, delay in graft function, serum creatinine at the end of follow-up and renal graft survival. Results: Patients with chronic hypotension who undergo transplantation present a clear tendency to a higher rate of primary non-function of the graft (15.4% vs 7.7%) and more venous thrombosis of the graft (13.5% vs 3.8%). although without reaching statistical significance. These patients presented more frequently delayed graft function (71.2% vs 44.2%, p <0.001), it took more days to spontaneously lower serum creatinine (14.8 days vs 7.7 days, p < 0.001) and required a greater number of dialysis sessions (3.5 sessions vs 1.6 sessions, p <0.001). Serum creatinine at the end of follow-up was higher in the hypotensive group (2.2 vs 1.6, p = 0.037), who showed a tendency to lower graft survival (64% at 60 months vs. 84% at control group) but without achieving statistical significance (p = 0.079). Conclusions: Chronic hypotension seems to be an important factor in the immediate evolution of the renal graft as well as in its long-term function. The identification of these patients could be of vital importance in order to implement therapeutic measures that improve transplant result.